PENGEMBANGAN MEDIA BOOKCREATOR MENGGUNAKAN MODEL PROBLEM BASED LEARNING PADA PEMBELAJARAN IPAS DI KELAS V SEKOLAH DASAR - Khairumi, Fadila; Erita, Yeni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the lack of media that is interesting and motivating for students to learn, and the use of technology-based learning media has not been optimally used by teachers. The purpose of this development research is to develop e-book media based on Bookcreator in grade V of elementary schools that is valid, practical and effective. This research method is Research and Development (R&D), with the ADDIE model consisting of five stages, namely, analysis, design, development, implementation, and evaluation. This research was conducted in elementary schools, and data were collected using questionnaires given to material experts, media experts, and language experts, as well as teacher and student response questionnaires. This research was conducted on grade V students at UPT SDN 05 Pasar Baru, UPT SDN 10 Koto Jua, and UPT SDN 02 Pasar Baru. The results of this development research are e-book learning media that obtained validation results for material, media, and language with an average of 82.33%, including the very valid category. The practicality of the teacher response questionnaire at UPT SDN 05 Pasar Baru obtained a percentage of 94% and the student questionnaire obtained a percentage of 94.02%, at UPT SDN 10 Koto Jua obtained a percentage of 96% (teachers) and 93.5% (students), UPT SDN 02 Pasar Baru obtained a percentage of 94% and students obtained a percentage of 95.39%. The results of the effectiveness test of students after learning using e-book learning media, at UPT SDN 05 Pasar Baru amounted to 88.88%, UPT SDN 10 Koto Jua amounted to 88% and UPT SDN 02 Pasar Baru amounted to 94.73%. Thus, the e-book learning media based on Bookcreator with a problem-based learning model in science learning in grade V of Elementary School is declared valid, practical, and effective.